89 Incidence and Risk Factors for Prolapse in Spanish Female Breeding Pig Herds. (10th April 2018) - Iida, R; Piñeiro, C; Koketsu, Y
Abstract: Prolapse in female breeding pigs is an emerging concern for pig production. Our objectives were to estimate incidence rate of prolapse and to determine risk factors associated with prolapse occurrences. Data included 905, 089 service records in 819, 754 parity records of 155, 238 female pigs from 144 swine herds in Spain. Removal reasons and removal date were used to define a prolapse problem. A 1:3 matched case-control study was carried out and piecewise exponential models were applied to the data to investigate prolapse risk factors. The following factors were assessed: age at first service, parity, number of services, service season and weeks after service. The following time dependent variables were also included in the model: previous gestational length, total number of pigs born and stillborn and mummified piglets for serviced females. Almost 1% of females (0.8%) were removed due to prolapse (95% confidence interval: 0.75-0.84%), and the overall annualized prolapse incidence rate was 3.8 cases per 1, 000 pig-years (95% confidence interval: 3.59-4.01). Factors that increased the risk of pig prolapse were the 16 th week after service, being in parity 3 or higher, re-service, servicing in summer, autumn or winter, short previous gestational length and 2 or more stillborn piglets ( P ≤ 0.04). For example, the prolapse hazard was 30.8 times higher in the 16 th week after service than in weeks 0-14 ( P < 0.01). Also, the prolapse hazard was 1.6-1.9 times higher in parity 3 or higher sows than in gilts ( P < 0.01), and 1.2 times higher in re-serviced pigs than in first serviced pigs ( P = 0.04). It was also 1.3-1.5 times higher in females serviced in summer, autumn or winter than in females serviced in spring ( P < 0.05), and 1.3-1.4 times higher in sows with up to 113 days gestational length than in sows with 114 days or longer gestational length ( P < 0.01). Lastly, prolapse hazard was also 1.4 times higher in sows with two or more stillborn piglets than in sows with no stillborn piglets ( P < 0.01). However, there were no associations between removal due to prolapse and any other factors, including age at first service ( P = 0.30), total number of pigs born ( P = 0.06) and mummified piglets ( P = 0.32). Therefore, to reduce the risk of prolapse removals producers should try to identify prolapse occurrences at an early stage by paying attention to at-risk female pigs in peripartum periods.